2021
DOI: 10.1088/2515-7647/abdb04
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in structured illumination microscopy

Abstract: Structured illumination microscopy (SIM), is a wide-field, minimally-invasive super-resolution optical imaging approach with optical sectioning capability, and it has been extensively applied to many different fields. During the past decades, SIM has been drawing great attention for both the technique development and applications. In this review, firstly, the basic conception, instrumentation, and functionalities of SIM are introduced concisely. Secondly, recent advances in SIM which enhance SIM in different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…We thus investigated whether this effect on the microtubules might interfere with organelles, such as lysosomes, mitochondria, and ER, as the microtubules are important for the positioning, formation, fission, and fusion of the latter (Mattenberger et al, 2003; Pu et al, 2016). We applied super-resolution 2-colour structured illumination microscopy (SIM) with a resolution of 100 nm (i.e., below the diffraction limit) (Young et al, 2016) in COS7 cells, which have a flat morphology ideal for SIM, as the technique is sensitive to out-of-focus glare associated with thicker samples (Ma et al, 2021). We show that clustering of lysosomes and mitochondria at the perinuclear area of cells is greater in P525L-, compared to WT-FUS and control cells ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…We thus investigated whether this effect on the microtubules might interfere with organelles, such as lysosomes, mitochondria, and ER, as the microtubules are important for the positioning, formation, fission, and fusion of the latter (Mattenberger et al, 2003; Pu et al, 2016). We applied super-resolution 2-colour structured illumination microscopy (SIM) with a resolution of 100 nm (i.e., below the diffraction limit) (Young et al, 2016) in COS7 cells, which have a flat morphology ideal for SIM, as the technique is sensitive to out-of-focus glare associated with thicker samples (Ma et al, 2021). We show that clustering of lysosomes and mitochondria at the perinuclear area of cells is greater in P525L-, compared to WT-FUS and control cells ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of imaging improvements, the performance of cell segmentation would be enhanced in a C. elegans strain that expressed a more uniform and brighter membrane tag across developmental stages and cell types than current strains. In addition, compared with confocal microscopy, L ight S heet F luorescence M icroscopy (LSFM) has a faster imaging speed and causes less phototoxicity and photobleaching, while S tructured I llumination M icroscopy (SIM) has a resolution approaching the diffraction limit [136] , [137] , [138] , [139] . Thus, to further improve the performance of segmentation, image acquisition should be explored using LSFM-based and SIM-based imaging systems that have been developed and adapted for C. elegans embryogenesis, such as inverted selective plane illumination microscopy, dual-view inverted selective plane illumination microscopy, and instant structured illumination microscopy [111] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] .…”
Section: Cellular-resolution Studies Of Embryogenesismentioning
confidence: 99%
“…The resolution gain comes at the cost of overall longer exposure times per image and increased exposure of the sample to light, which increases photobleaching. More recent implementations like iSIM (instant Structured Illumination Microscopy) overcome this limitation through an analog implementation [117], and the technique has been improved to allow multicolor and 3D imaging [118]. Rey et al showed using iSIM (instant Structured Illumination Microscopy) that chemical inhibition of actin nucleators and the actin nucleation promoting factor N-WASP results in a reduction of actin dynamics as well as BCR motility [17].…”
Section: Accepted Articlementioning
confidence: 99%
“…The resolution gain comes at the cost of overall longer exposure times per image and increased exposure of the sample to light, which increases photobleaching. More recent implementations such as iSIM (instant structured illumination microscopy) overcome this limitation through an analog implementation [117], and the technique has been improved to allow multicolor and 3D imaging [118]. Rey et al .…”
Section: Emerging Microscopy and Analysis Techniques Provide New Insi...mentioning
confidence: 99%